Utility of the Questionnaire on Children’s Processing of Sensory Input in Children with Autism Spectrum Disorder - Gričar, Nevenka; Gosar, David (Revija za elementarno izobraževanje, 2023)
In addition to difficulties with social communication and behaviour flexibility, children with autism spectrum disorder (ASD) often experience difficulty responding to sensory input. Our aim was to assess the sensitivity of the Questionnaire on Children’s Processing of Sensory Input to sensory issues experienced by children with ASD. Based on the responses of 108 parents of neurotypical children and 27 parents of children with ASD (3 to 10 years), we found that the questionnaire differentiated well between the groups. The questionnaire may be used by health, education or social services professionals and represents a novel tool for recognizing sensory processing difficulties in children. Information gained from it can help plan additional supports for children with sensory challenges.
Keywords: sensory integration, assessment, sensory processing disorder